Molecular simulation for thermoelectric properties of c-axis oriented hexagonal GeSbTe model clusters - Athorn Vora-ud (2018)
© 2015 Elsevier Ltd. Using a combination of molecular orbital and molecular dynamics simulations, electronic and thermoelectric properties of GeSbTe model clusters are presented. The unit cells of Ge13Sb20Te52, Ge7Sb12Te40and Ge14Sb6Te26model clusters are designed corresponding to GeSb2Te4, GeSb4Te7and Ge2Sb2Te5compositions in hexagonal phase, oriented in the c-axis direction. The electronic structures of clusters have been simulated by discrete-variational molecular orbital calculation using Hartree-Fock-Slater approximation to determine the electrical conductivity and Seebeck coefficients in Mott expression. For thermal properties, molecular dynamics simulations have been employed on clusters in amorphous, cubic and hexagonal phases using Verlet's algorithm and subsequently using Green-Kubo relation for lattice thermal conductivity. We assumed inter-atomic interaction, defined by the Morse-type potential function added to Busing-Ida potential function, which considers partial electronic charges on the ions, bond length of the cation-anion pair, and depth and shape of the potential. Based on our simulations, detailed variation of electrical conductivity, carrier thermal conductivity, lattice thermal conductivity, Seebeck coefficients, power factor and figure of merit, are presented as a function of temperature in 300-700 K range. Thermoelectric parameters obtained in present study were compared and explained with those of experimentally results of Ge2Sb2Te5composition in hexagonal phase.